Pengaruh penerapan model pembelajaran teaching factory terhadap kesiapan berwirausaha - Dian Herdiana Utama; B Lena Nuryanti; Nadia Agustina (Journal of Business Management Education (JBME), 2020)
The teaching factory learning model is an integrated learning model. Entrepreneurship education is a process of learning to instill entrepreneurial values through habituation and maintenance of behavior and attitudes. Through the teaching factory learning model that is supported by learning entrepreneurship, students are expected to have readiness for entrepreneurship. The application of teaching factory teaching model aims to form student competencies through the unit of the school environment unit based on industry and supported by the implementation of entrepreneurial learning in the formation of an entrepreneurial mentality. This article examines the effect of the application of the Teaching Factory Learning Model to entrepreneurial readiness in class XI students of the Online Business and Marketing Program at SMKN 1 Bandung. The research method used in this research is descriptive and verification methods using path analysis.